지역사회에서 회복중인 알코올중독자의 스트레스와 대처 - 정재원(Jaewon Joung); 강경림(KyungIm Kang) (Seuteureseu yeon-gu (Online), 2019)
이 연구는 회복중인 알코올중독자의 스트레스와 대처 탐색을 위한 질적 연구로 참여자와의 개별면담은 내용분석법으로 분석하였다. 연구결과 ‘술없이 마주하게 된 삶의 문제와 스트레스’, ‘끊임없는 변화의노력과 성장’이라는 범주와 스트레스의 하위 범주로 ‘술로 인해 쇠약해진 몸’, ‘긴장을 늦출 수 없는 음주의 유혹’, ‘과거에 대한 아픈 회한’, ‘새로운 관계 맺음의 어려움’, ‘홀로 남은 고독한 삶’, ‘멀고 먼 자립의 길’이 대처의 하위 범주로 ‘함께함의 강력한 힘’, ‘따뜻하게 품어주는 가족의 지지’, ‘끊임없이 다져보는 굳건한 의지’, ‘내려놓음의 치유력’, ‘배움을 통한 알아차림’, ‘음주를 대체할 다양한 활동참여’가 도출되었다. 이 결과는 대상자의 재발예방과 회복유지를 위한 유용한 정보로 활용될 수 있을 것이다. Background: The purpose of this qualitative study is to identify stresses and coping of recovering alcoholics in communities. Methods: Individual interviews were conducted with a total of 8 recovering alcoholics. Data were analyzed using qualitative content analysis. Results: Two categories and six subcategories for each category were derived. Two categories were ‘life problems and stresses encountered without drinking’ and ‘constant change efforts and growth’. The identified stresses of the participants were summarized as ‘a body weakened by drinking’, ‘constant vigilance against the ongoing temptation of drinking’, ‘painful regrets for the past’, ‘difficulties in building new relationships’, ‘a lonely life left alone’, ‘a long way to self-reliance’. In addition, the revealed helpful factors in coping with the stresses were ‘strong power by being together’, ‘strong family support’, ‘firm wills constantly strengthened’, ‘healing power of letting-go’, ‘awareness through learning’, ‘participation in various activities to replace drinking’. Conclusions: Participants were experiencing various stresses caused by physical, mental and social problems in their recovery process and trying to overcome the difficulties by applying various methods. The results of this study may provide significant information to prevent relapse and maintain the recovery process of alcoholics. KCI Citation Count: 2